Gatos no forno: memória, identidade cultural e imigração - Comitti, Leopoldo (Aletria: Revista de Estudos de Literatura, 1995)
This essay carries out a reading of writings by immigrants and their descendants. It tries to establish connections to their literary expression, their nationalistic utopia and their ambiguous cultural identity.